Acupuncture improves the symptoms, serum ghrelin, and autonomic nervous system of patients with postprandial distress syndrome: a randomized controlled trial - Zi-tong Fu; Cun-zhi Liu; Mi-Rim Kim; Yi-duo Liu; Yu Wang; Yi-Ming Fu; Jing-Wen Yang; Na-Na Yang (BMC, 2024)
Abstract Background Whether gastrointestinal hormones in patients with postprandial distress syndrome (PDS) are altered by acupuncture, and whether such alterations are related to the autonomic nervous system (ANS), remains an open question. Objective This study aims to investigate the effects of acupuncture on symptoms, serum hormones, and ANS in PDS patients. Methods This randomized controlled clinical trial was conducted at Beijing Hospital of Traditional Chinese Medicine affiliated with Capital Medical University. Sixty-two PDS patients were randomly assigned equally to acupuncture or sham acupuncture arm (3 sessions per week for 4-week). The main outcome measures which were evaluated at baseline and 4-week included cardinal symptoms, serum hormones including ghrelin, vasoactive intestinal peptide (VIP), substance P (SP), and ANS. Results Among the 62 randomly assigned participants, 51 (82%) were included in the baseline characteristics and outcome analysis. Gastrointestinal symptoms including response rate (p = 0.001) and dyspepsia symptom severity (p = 0.002) were significantly improved after acupuncture treatment. Serum ghrelin concentration was significantly higher in acupuncture group than in sham acupuncture group (8.34 ± 3.00 ng/ml versus 6.52 ± 2.00 ng/ml, p = 0.022) after 4-week treatment, instead of VIP and SP (p > 0.05). The acupuncture group had significantly higher vagal activity, showing with increasing of high-frequency component (HF, p ≤ 0.001) and decreasing of the ratio of low-frequency and HF (p ≤ 0.001). In relationship analysis, the HF component exhibited a significant inverse correlation with symptom severity (R = − 0.501, p ≤ 0.001), but not with ghrelin level (R = 0.026, p = 0.865). Conclusion Acupuncture may improve the symptoms and increase the ghrelin level of PDS patients, the therapeutic effect of acupuncture was associated with the alteration of vagal activity. Trial registration: The trial is registered with the ISRCTN registry, ISRCTN12511434. Registered 31 March 2017, https://www.isrctn.com/ .